Clopidogrel Versus Ticagrelor or Prasugrel After Primary Percutaneous Coronary Intervention According to CYP2C19 Genotype: A POPular Genetics Subanalysis - Claassens, Daniel M.F.; Bergmeijer, Thomas O.; Vos, Gerrit J.A.; Hermanides, Renicus S.; van ’t Hof, Arnoud W.J.; van der Harst, Pim; Barbato, Emanuele; Morisco, Carmine; Tjon Joe Gin, Richard M.; Asselbergs, Folkert W.; Mosterd, Arend; Herrman, Jean-Paul R.; et al. (Circulation. Cardiovascular interventions, 2021)
[Figure: see text].